Motivasi Ibu Nifas dalam Perawatan Payudara di Wilayah Kerja Puskesmas Tegalrejo Kabupaten Magelang Tahun 2013 - Evy Ernawati; Ninik Rosidah (LPPM STIKES Guna Bangsa, 2017)
Background: Breast Care during childbirth was a requirement for the mother who had just given birth. Breast care after childbirth aims so that the breasts are always clean and easy on the suction by the baby. Objective: find out how mothers motivation in the picture doing breast care at the work-area Clinics Tegalrejo Magelang Regency by 2013. Methods: research method used is descriptive research with cross sectional approach. Sampling method in this research is purposive sample with the total sample as many as 62 respondents. Results: based on the results tabulate the data characteristics of parturition results obtained the age of mother mother childbirth most are aged 20-35 years old that is as much as 55 (88.7%) respondents, educational level of the mother most is how SD that is as much as 29 (46,8%) respondents, most mothers work parturition is a housewife that is as much as 55 (88.7%) respondents, mother childbirth most income is Rp 942,000 Rp 1,500,000 – i.e. as many as 56 (90.3%) respondents While the distance of the Home Ministry with parturition mother most is enough that is as much as 54 (87,1%) respondents, and how the mother do most ANC visit was ≥ 4 times that is as much as 60 (96.8%) respondents. Conclusion: most of the parturition's mother has a high motivation in doing breast care